Fluorescent zwitterionic Iridium(III) complexes containing sulfonate groups: synthesis, biological activity and tracking in live cells. (May 2020) - Yang, Yanjing; Guo, Lihua; Ge, Xingxing; Chen, Wenjing; Zhou, Huanxing; Zhu, Teng; Li, Xin; Tuo, Shujing; Liu, Zhe
Abstract: Fluorescent zwitterionic iridium complexes have been rarely reported. In this work, four fluorescent zwitterionic cyclometalated iridium complexes bearing different sulfonated iminopyridine ligands (Ir1 –Ir4 ) were synthesized. The solid-state molecular structure of Ir1 was established by X-ray crystallography. These zwitterionic complexes are very stable in aqueous solution and have a detectable fluorescence. The structure-activity relationship toward cancer cells was observed for these complexes. Further, the fluorescence properties of these zwitterionic complexes make it possible to determine their microscopic mechanism by the cell imaging. It is noteworthy that complex Ir3 can specifically and effectively target lysosomes and induce cell death by damaging lysosomes Further, the energy-dependent pathway was involved in the uptake of Ir3 in cancer cells. In addition, the modes of cell death were also studied through flow cytometry experiments. It seems that Ir3 displayed their biological efficacy by cell-cycle arrest and the induction of cell apoptosis. Graphical abstract: A series of fluorescent zwitterionic cyclometalated iridium(III) complexes containing sulfonated iminopyridine ligands were synthesized. Their structure-activity relationship toward cancer cells and confocal microscopy imaging were investigated. Image 1 Highlights: A series of fluorescent zwitterionic cyclometalated iridium(III) complexes have been synthesized and characterized. Significant structure-activity relationship was observed for these complexes. These complexes could accumulate in lysosomes and induce lysosomal damage.